SEKSUALITAS PEREMPUAN DALAM KITAB FATHU AL-IZAR FI KASYFI AL-ASRAR AL-AWQAT AL-HARTSI WA KHILQAH AL-ABKAR - Bannan Naelin Najihah (AL-IBANAH, 2021)
This study aims to dissect women's sexuality in the book Fathu Al-Izar fi Kasyfi Al-Asrar Al-Awqar Al-Hartsi wa Khilqah Al-Abkar using the literature review method. The lack of Islamic sex education literature makes this book the foremost book studied in the traditional Islamic boarding school. There are several dimensions of female sexuality in each section of the discussion. But in general it centers on the last section of the discussion, "Bayan Asrar Khilqah Al-Abkar" (virgin secret explanation). This book generally uses a physiognomic science approach to explain the biological dimensions of female sexuality regarding vaginal anatomy and the high and low levels of female sexual desire.